2018
DOI: 10.3390/w10111536
|View full text |Cite
|
Sign up to set email alerts
|

Flood Prediction Using Machine Learning Models: Literature Review

Abstract: Floods are among the most destructive natural disasters, which are highly complex to model. The research on the advancement of flood prediction models contributed to risk reduction, policy suggestion, minimization of the loss of human life, and reduction the property damage associated with floods. To mimic the complex mathematical expressions of physical processes of floods, during the past two decades, machine learning (ML) methods contributed highly in the advancement of prediction systems providing better p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
604
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 1,025 publications
(618 citation statements)
references
References 218 publications
(343 reference statements)
5
604
0
9
Order By: Relevance
“…There are many different ANN architectures used for hydrological modeling, such as the backpropagation neural network (Sajikumar & Thandaveswara, 1999) and recurrent neural networks (RNNs) (Nagesh Kumar et al, 2004). Although robust ANN model development approaches are still needed (Maier et al, 2010), studies have shown that ANNs can predict the runoff more accurately than can the classical regression models (Mosavi et al, 2018;Riad et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are many different ANN architectures used for hydrological modeling, such as the backpropagation neural network (Sajikumar & Thandaveswara, 1999) and recurrent neural networks (RNNs) (Nagesh Kumar et al, 2004). Although robust ANN model development approaches are still needed (Maier et al, 2010), studies have shown that ANNs can predict the runoff more accurately than can the classical regression models (Mosavi et al, 2018;Riad et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The hybridization of machine learning methods has shown to be an essential approach to improve the performance of the prediction models. For the future research, advancement of hybrid and ensemble machine learning models, e.g., [23][24][25][26][27][28], and comparative analysis with deep learning models, e.g., [29][30][31][32] are proposed to identify models with higher efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The ANFIS-PSO model with the RMSE of 0.0065, MAE of 0.0028, and R2 equal to 0.9999, with a minimum deviation of 0.0691 (KJ/s), outperforms the ANFIS-GA and single ANFIS models. For the future research, advancement of hybrid and ensemble machine learning models, e.g., [47][48][49][50][51][52], and comparative analysis with deep learning models, e.g., [53][54][55][56] are proposed to identify models with higher efficiency.…”
Section: Resultsmentioning
confidence: 99%